Biological potency of actinomycetes extracts from rhizosphere soil of Dacrycarpus imbricatus from Toba Samosir, North Sumatra - Praptiwi, Ahmad Fathoni, Ade Lia Putri, Dewi Wulansari, Andria Agusta, (Journal of Applied Pharmaceutical Science, 2023)
Plants, including Dacrycarpus imbricatus, have important ecological functions as a carbon source, support the soil microbial community, improve soil nutrients, and conserve water. Moreover, actinomycetes in rhizospheric soil have a high potential in producing bioactive compounds, including anti-bacterial and antioxidant compounds. This study investigated 11 actinomycetes extracts for their anti-bacterial activity against Escherichia coli and Staphylococcus aureus and antioxidant activity as the 2,2-diphenyl-1-picrylhydrazyl (DPPH-free radical scavenging. Actinomycetes strains were isolated from the rhizosphere soil of D. imbricatus. Anti-bacterial and DPPH scavenging activities were carried out by thin-layer chromatography-bioautography. Besides, the microdilution method was performed to determine IC50 and minimum inhibitory concentration values. Potential strains were identified based on molecular identification and tested for their anti-bacterial activity against Mycobacterium smegmatis. Results revealed that the highest anti-bacterial activity exhibited by two actinomycetes extracts, Streptomyces avermitilis A18TE-8 and Micromonospora terminaliae A18TE1-1, had moderate-strong anti-bacterial activity against S. aureus (8 and 128 μg/ml, respectively) and the percentage of growth inhibition against M. smegmatis was moderate (80% and 60%, respectively). Two extracts of actinomycetes M. terminaliae A18TE1-1 and Streptomyces nigrescens A18TE1-9 had a moderate antioxidant activity with IC50 values 122.96 and 98.79 μg/ml, respectively (or AAI values 0.25 and 0.31, respectively). Therefore, actinomycetes extracts from D. imbricatus rhizosphere soil could be anti-bacterial sources, especially against S. aureus and M. smegmatis, rather than antioxidant sources.
Keywords: Actinomycetes, anti-bacterial, DPPH scavenging activity, Dacrycarpus imbricatus, phylogenetic analysis